Mining practices in Indonesia: The role of agrarian law in land grabbing and the elimination of indigenous peoples' rights - Prestiwi, Adinda Dwi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The relationship between nature and society is an ecological unity that is mutually formed. However, in the historical premise of capitalism, man is separated from nature and placed in relations of production that make nature an object of exploitation for the accumulation of capital. In Indonesia, the expansion of extractive industries, particularly mining, does contribute to national economic growth, but at the same time results in structural land grabbing, especially in indigenous territories. This study aims to examine the practice of mining as a manifestation of the capitalist system that perpetuates agrarian injustice, deprivation of land rights, and the marginalization of Indigenous Peoples. Methods: The research uses qualitative method through literature review and comparative-descriptive case study with socio-legal approach to examine the relationship between socio-ecological reality due to mining and agrarian legal framework. Data were obtained from Scopus and Web of Science indexed journals, ecological perspective books, and NGO and institutional reports. The analysis was carried out using Marxist ecological theory, which views capitalism as treating nature as an unlimited resource that can be exploited, as well as agrarian law theory, which asserts that the earth, water, and natural resources must be controlled by the state for the greatest prosperity of the people. Findings: The findings show that the hegemony of the mining industry in Papua, North Maluku, NTT, and Sumatra is causing the loss of indigenous peoples' living space, resulting in increased poverty and decreased health quality, as well as triggering ecological damage such as deforestation and river pollution. This condition is consistent with the Marxist ecological perspective that capitalism encourages degrarianization and creates ecological disharmony through the expansion of extractive industrial production space. In addition, formal agrarian law often fails to protect indigenous peoples' rights to land as living space. Conclusion: In conclusion, capitalism transforms nature from a living space into an object of production, while the role of the state that facilitates extractive industries reinforces structural inequality and ignores the mandate of Agrarian Justice in Article 2 point 3 of the 1960 Constitution. Novelty/Originality of this article: The novelty of this study lies in integrating Marxist ecological theory with agrarian law analysis to reveal how capitalism and state-facilitated mining perpetuate indigenous dispossession and ecological degradation in Indonesia.